AGAINST ALL ODDS (PERGESERAN STANDAR KECANTIKAN DALAM IKLAN KORPORAT â€œREAL BEAUTYâ€ DOVE) - Emyliani, Tania; Krisdinanto, Nanang; Akhsaniyah, Akhsaniyah (Universitas Serang Raya, 2019)
This study looked at how the matching of signs related to the shift in standard of beauty incorporate advertising